A welfare perspective on the fiscal-monetary policy mix: The role of alternative fiscal instruments - Luigi Marattin; Massimiliano Marzo; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
The need of fiscal consolidation is likely to dominate the policy agenda in the next decade; starting from statistical evidence on the conduct of fiscal policy in the EMU area over the last decade, this paper addresses the optimality of alternative fiscal consolidation strategies. We explore the welfare properties. In this paper we explore the welfare properties of debt-targeting fiscal policy implemented through, alternatively, distortionary taxation on consumption, labour and capital income or productive and wasteful government expenditure. We build a general equilibrium model with various distortions in order to evaluate the welfare ranking of alternative fiscal policy configurations under different monetary policy regimes. Our results show the welfare superiority of fiscal adjustments based on productive government expenditure, whereas the use of a capital income tax rate as fiscal instruments yields the highest welfare loss.
Keywords: E61; E62; E63; 330